2015
DOI: 10.1155/2015/475340
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Research Utilization among Registered Nurses in Traditional Chinese Medicine Hospitals: A Cross-Sectional Survey in China

Abstract: Background. As there might be relevant differences with regard to research utilization in the general hospitals, we aimed to study research utilization among registered nurses working in traditional Chinese medicine hospitals. Methods. A total of 648 registered nurses from 4 tertiary-level hospitals in China were recruited for participation. A modified BARRIERS Scale and self-designed questionnaires were used for data collection. Data were analyzed with descriptive statistics, t-tests, and one-way ANOVAs and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
8
23
1
Order By: Relevance
“…Meanwhile, constructivist grounded theory also emphasising on revealing patterns and connections rather than to linear reasoning and emphasises understanding rather than explanation (Charmaz, ). In this study, we found the factors ranging from the evidence level, nurses level, patient level, system level and outside system level, which were generally consistent with the literature from other countries (Ploeg, Davies, Edwards, Gifford, & Miller, ; Solomons & Spross, ; Yagasaki & Komatsu, ), as well as the previous published Chinese surveys (Chien et al., ; Wang et al., ; Zhou et al., ). However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence‐based nursing.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Meanwhile, constructivist grounded theory also emphasising on revealing patterns and connections rather than to linear reasoning and emphasises understanding rather than explanation (Charmaz, ). In this study, we found the factors ranging from the evidence level, nurses level, patient level, system level and outside system level, which were generally consistent with the literature from other countries (Ploeg, Davies, Edwards, Gifford, & Miller, ; Solomons & Spross, ; Yagasaki & Komatsu, ), as well as the previous published Chinese surveys (Chien et al., ; Wang et al., ; Zhou et al., ). However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence‐based nursing.…”
Section: Discussionsupporting
confidence: 91%
“…Two of the studies were carried out in general hospitals (Chien, Bai, Wong, Wang, & Lu, ; Wang, Jiang, Wang, Wang, & Bai, ). The third one was conducted in traditional Chinese medicine hospitals (Zhou et al., ). The results of the three studies consistently pointed out that Chinese nurses perceived higher and more diverse barriers than those reported in studies from in Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no close collaboration between clinical practices and nursing schools. Traditional practices not promote positive attitude for the improvement of clinical training (Zhou et al, 2015). The nursing education system does not offer theoretical content related to clinical requirement.…”
Section: Introductionmentioning
confidence: 99%